2021
DOI: 10.1016/j.gpb.2021.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell RNA Sequencing Reveals Sexually Dimorphic Transcriptome and Type 2 Diabetes Genes in Mouse Islet β Cells

Abstract: Type 2 diabetes (T2D) is characterized by the malfunction of pancreatic β cells. Susceptibility and pathogenesis of T2D can be affected by multiple factors, including sex differences. However, the mechanisms underlying sex differences in T2D susceptibility and pathogenesis remain unclear. Using single-cell RNA sequencing (scRNA-seq), we demonstrate the presence of sexually dimorphic transcriptomes in mouse β cells. Using a high-fat diet-induced T2D mouse model, we identified sex-dependent T2D altered genes, su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 67 publications
1
24
0
Order By: Relevance
“…These data therefore support the notion that sex plays a pivotal role in the pathophysiology of T2DM and thus may be an important factor to consider when opting for personalized T2DM management. However, the two sexes share some aspects of the disease pathogenesis since sex-independent DEGs involving several disease-specific processes were also demonstrated [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…These data therefore support the notion that sex plays a pivotal role in the pathophysiology of T2DM and thus may be an important factor to consider when opting for personalized T2DM management. However, the two sexes share some aspects of the disease pathogenesis since sex-independent DEGs involving several disease-specific processes were also demonstrated [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because many of these genes may have been missed if the scRNAseq data was not analyzed by sex, our findings advance our understanding of β cell changes in T2D by identifying additional genes that are differentially regulated in this context. This knowledge adds to a growing number of studies that identify sex differences in β cell gene expression during aging in humans ( 40 ), and in mice fed either a normal ( 32, 33 ) or a high fat diet ( 32 ). Further, given that our RNAseq on islets from male and female mice with equivalent insulin sensitivity identifies genes and biological pathways that align with previous studies on sex differences in murine β cell gene expression ( 32, 33 ), our data suggests that sex differences in islet and β cell gene expression cannot be explained solely by a male-female difference in peripheral insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…This knowledge adds to a growing number of studies that identify sex differences in β cell gene expression during aging in humans ( 40 ), and in mice fed either a normal ( 32, 33 ) or a high fat diet ( 32 ). Further, given that our RNAseq on islets from male and female mice with equivalent insulin sensitivity identifies genes and biological pathways that align with previous studies on sex differences in murine β cell gene expression ( 32, 33 ), our data suggests that sex differences in islet and β cell gene expression cannot be explained solely by a male-female difference in peripheral insulin resistance. Instead, there is likely a basal sex difference in the β cell gene expression landscape that forms the foundation for sex-specific transcriptional responses to ER stress, and T2D.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also as an application-oriented work, Hu et al demonstrated that miRNAs are important posttranscriptional regulators for reducing gene expression noise and conferring robustness to biological processes through the integrated analysis of single-cell RNA and miRNA expression profiles [18] . Moreover, Liu et al elucidated sexual dimorphism in type 2 diabetes (T2D) pathogenicity and provided novel insights towards the development of precision medicine in T2D [19] . Li et al provided a valuable resource for understanding embryonic osteogenesis and angiogenesis underlying vertebrate thoracolumbar vertebra (TLV) and rib primordium (RP) development at the cell type-specific resolution, which offers a comprehensive view on the transcriptional profile of animal embryonic development [20] .…”
mentioning
confidence: 99%